EVALUATION OF PERFORMANCE AND STABILITY OF SUNFLOWER GENOTYPES AGAINST SALINITY STRESS - S. S. Ali; Z. Manzoor T. H. Awan; S. S. Mehdi (Journal of Animal and Plant Sciences, 2006)
The performance of four sunflower cultivars along with their six F1 hybrids, was evaluated over three salinity levels at Agricultural University, Faisalabad during 1998-1999. The mean values of oil yield per plant, oil and protein percentage of the genotypes were examined for which significant genotype-environment interactions were detected. Stability statistics based on Eberhart and Russell approach were estimated for all the varieties and traits. KNI possessed maximum mean oil yield per plant and oil percentage but low protein percentage whereas Suncom 110 showed high mean protein percentage. The results indicated that cultivars Suncom 90 and Suncom 110 were stable for oil percentage whereas genotypes KNI showed stability in its performance for oil yield per plant and protein percentage due to the mean above the grand mean and values of b1 and S2d non-significantly different from 1.0 and 0.0, respectively. The antagonistic relationship between mean yield of the genotypes and their stability statistics was observed, reconciliation is not need to made between yield and stability statistics.
Keywords: Stability; oil yield; Hellianthus annuus; salinity.